THE ROLE OF PHYSICAL EDUCATION AND SPORTS IN THE EDUCATION OF CHILDREN AND ADOLESCENTS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
One of the priorities of our society is the importance of creating a healthy lifestyle, improving the health of the nation’s gene pool, and raising a healthy generation through physical education and sports.